Degradation of permafrost beneath a road embankment enhanced by heat advected in groundwater 1 This article is one of a series of papers published in this CJES Special Issue on the theme of Fundamental and applied research on permafrost in Canada. - de Grandpré, Isabelle; Fortier, Daniel; Stephani, Eva (Canadian Journal of Earth Sciences, 2012)
For the past few decades, northwestern North America has been affected by climate warming, leading to permafrost degradation and instability of the ground. This is problematic for all infrastructure built on permafrost, especially roads and runways. Thaw settlement and soil consolidation promote embankment subsidence and the development of cracks, potholes, and depressions in road pavement. In this study, we investigate highway stability in permafrost terrain at an experimentally built road embankment near Beaver Creek, Yukon. A network of 25 groundwater monitoring wells was installed along the sides of the road to estimate groundwater flow and its thermal impact on the permafrost beneath the road. Data on topography, water-table elevation, ground temperature, and stratigraphy of the soil were collected at the site. The geotechnical properties of each soil layer were determined by laboratory analysis and used to calibrate a two-dimensional groundwater flow model. Field observations showed that water was progressively losing heat as it flowed under the road embankment. Our results suggest that advective heat transfer related to groundwater flow accelerated permafrost degradation under the road embankment.